THE EFFECTIVENESS TEST OF PULP MACERATION (Mimusops elengi L) ON BACTERIAL GROWTH NORMAL MICROFLORAS OF MOUTH - Nelma Hasibuan; Mardan Ginting; Suryani MF Situmeang (Alliance oh Health Activists (AloHA), 2021)
Tanjung or Mimusops elengi L. tree is a member of the Sapotaceae tribe which is known as a evergreen tree. So far, the headland has only been used as a shade planted in parks and on the side of the road, even though the headland has a number of health benefits. Flora in the oral cavity basically has a harmonious relationship with the host and consists of a variety of organisms, including bacteria, fungi, mycoplasma, protozoa, and viruses that can be encountered from time to time. The research objective was to determine whether the ethanolic extract of Tanjung (Mimusops elengi L) fruit had anti-bacterial inhibition against oral microflora. This research was a true-experiment which aims to determine the possible cause and relationship effect of one or more groups being studied. The research was carried out in several locations of Tanjung tree plants in Medan city, and secondary metabolite testing (Phytochemical Screening) was carried out at the Pharmacy Laboratory of North Sumatra university (USU) as well as at the Microbiology Laboratory of Poltekkes Medan. The research time started after receiving the title of the proposal until the final report. Improvement of the proposal until completion was estimated from November 2019 to July 2020. The population was cape plants in the city of Medan, and samples are taken from fruiting and ripe cape plants (red fruit) in the Medan Estate area. In the test phase for the extract's antibacterial activity, the inhibitory diameter data will be obtained for each of the tested bacteria at a certain concentration. Data were analyzed using the One Way ANOVA statistical test. Before the test was carried out, the normality test was carried out first to ensure that the data were normally distributed. In the 25% extract treatment, 50% of Tanjung fruit pulp against Staphylococcus aureus and Streptococcus mutans showed p value